2023
DOI: 10.34172/mejdd.2023.318
|View full text |Cite
|
Sign up to set email alerts
|

Value of Serological Biomarker Panel in Diagnosis of Atrophic Gastritis and Helicobacter pylori Infection

Abstract: Background: Gastric cancer is one of the most common types of cancer worldwide. Helicobacter pylori infection is clearly correlated with gastric carcinogenesis. Therefore, the use of a new non-invasive test, known as the GastroPanel test, can be very helpful to identify patients at a high risk, including those with atrophic gastritis, intestinal metaplasia, and dysplasia. This study aimed to compare the results of GastroPanel test with the pathological findings of patients with gastric atrophy to find a safe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The GastroPanel test is widely used for risk stratification 18 ; nonetheless, there are concerns regarding I/II ratios. Recent studies reported that I/II ratios did not correlate with the severity or location of atrophy when using the GastroPanel test 19,20 . Another study concluded that the GastroPanel test is insufficient for cancer screening because only 32.4% of gastric cancer patients showed low I/II ratios of <3 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GastroPanel test is widely used for risk stratification 18 ; nonetheless, there are concerns regarding I/II ratios. Recent studies reported that I/II ratios did not correlate with the severity or location of atrophy when using the GastroPanel test 19,20 . Another study concluded that the GastroPanel test is insufficient for cancer screening because only 32.4% of gastric cancer patients showed low I/II ratios of <3 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that I/II ratios did not correlate with the severity or location of atrophy when using the GastroPanel test. 19,20 Another study concluded that the GastroPanel test is insufficient for cancer screening because only 32.4% of gastric cancer patients showed low I/II ratios of <3. 21 In our study, low I/II ratios and high G-17 levels correlated well with atrophy and IM scores according to the Kyoto classification.…”
Section: Discussionmentioning
confidence: 99%